Pengembangan SDM Pegawai Bagian Pengadaan Barang dan Jasa Sekretariat Daerah Kabupaten Aceh Tengah - Lestari, Resi; Aisyah, Siti; Khairani, Cut (Universitas 17 Agustus 1945 Surabaya, 2023)
This research was conducted to analyze human resource development in the Procurement of Goods and Services Section of the Regional Secretariat of Aceh Tengah Regency. The problem identified in this study is the low performance of employees, which is evident from their abilities and levels of discipline within the Goods and Services Procurement Section of the Aceh Tengah Regency Secretariat. The research method is descriptive qualitative, utilizing documentation and interviews as research instruments. The results indicate that human resource development in the procurement of goods and services has yet to be consistently implemented. This is evidenced by the fact that only employees meeting government-mandated education and training requirements for goods and services procurement are afforded development opportunities. While efforts have been made in this regard, they have yet to be uniformly applied. One contributing factor is the restriction of human resource development efforts to employees possessing the requisite goods and services procurement certification, as stipulated by government policies. Consequently, despite some progress, the distribution of developmental opportunities remains unequal. In light of these findings, it is recommended that the Goods and Services Procurement Department provide uniform training to all employees, thereby eliminating discrepancies in skill levels. Additionally, there is a need to enhance the competence of each employee through both formal and informal education and training initiatives, to enhance overall employee performance and organizational effectiveness.